The American machine shop - Peck, R.J. (My University, 1897)
Introduction: A thorough and exhaustive treatment of this subject in all its details would require a work of several volumes. It can not be expected then, that in a paper of a few thousand words more than a rapid sketch covering the main features of the general machine shop and a few words upon some of the special machines can be given. Modern machine shop practice shows fully as well as any other field the wonderful development of the nineteenth century in industrial life. Machines that were up to date ten years ago are obsolete now. The machinist of all men must be ever on the alert for all the new devices for reducing labor cost of his product, or else find himself undersold by his more enterprising neighbor. The tendency of the present is toward the development of special machines—machines designed to do a special kind of work and to do that work with a precision and rapidity far surpassing the ordinary work of planer lathe and vise. One exception to this is the milling machine. The thousands of ways in which it may be applied to the making of small parts of form other than plane and cylindrical outline make it one of the most important machines of the modern shop.
Citation: Peck, R.J. The American machine shop. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Mechanical engineering; Machine shop; Machinery; Theses; Manuscripts (documents)